To work or not to work? The effect of child-care subsidies on the labour supply of parents - Tuomas Kosonen (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper studies the effect of child-care subsidies on parental labour supply. I use variation arising from changes in the municipality-specific supplement to Finnish child homecare allowance to identify the causal effect of subsidies on the labour force participation of parents. The variation in labour supply incentives is plausibly exogenous, since eligibility depends on municipal-level rules, but not on family income. Robustness checks indicate that the results are not driven by policy endogeneity or residential sorting. I find a robust result that 100 euros higher supplement per month reduces the maternal labour supply by 3 per cent.
Keywords: J22; J13; H22; 330; parental labour supply; child-care subsidies; participation elasticity; Kinderbetreuung; Familienleistungsausgleich; Wirkungsanalyse; Weibliche Arbeitskräfte; Arbeitsangebot; Finnland